Answer:
x^2 – 3xy + 2y^2
Step-by-step explanation:
Factor the following:
x^2 - 3 x y + 2 y^2
Hint: | Factor the quadratic x^2 - 3 x y + 2 y^2.
The factors of 2 that sum to -3 are -1 and -2. So, x^2 - 3 x y + 2 y^2 = (x - 1 y) (x - 2 y):
Answer: (x - y) (x - 2 y)
Answer:
China is about 17 times bigger than France.
Meanwhile, the population of France is ~67.1 million people. (1.3 billion more people live in China).
Step-by-step explanation:
Step-by-step explanation:
4 and 5 is one 20/25
Answer:
The roots of equations are as m = And n =
Step-by-step explanation:
The given quadratic equation is 2 x² + 6 x - 1 = 0
This equation is in form of a x² + b x + c = 0
Let the roots of the equation are ( m , n )
Now , sum of roots =
And products of roots =
So, m + n = = - 3
And m × n =
Or, (m - n)² = (m + n)² - 4mn
Or, (m - n)² = (-3)² - 4 ()
Or, (m - n)² = 9 + 2 = 11
I.e m - n =
Again m + n = - 3 And m - n =
Solving this two equation
(m + n) + ( m - n) = - 3 +
I.e 2 m = - 3 +
Or, m =
Similarly n =
Hence the roots of equations are as m = And n = Answer